The Internet as a public place and a place of committing a prohibited act: Comments regarding the judgment of the Supreme Court of the Republic of Poland, case ref. no. IV KK 296/17 - Kluza, Jan; Sączek, Konrad (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The paper concerns the analysis of the possibility for classifying the Internet as a public place, which is of extraordinary legal significance with regard to the fulfilment of the criteria of many prohibited acts. Such a statement was presented by the Supreme Court of the Republic of Poland in its judgment of 17 April 2018, case ref. no. IV KK 296/17. This paper attempts to assess the standpoint of the Supreme Court of the Republic of Poland and the way it is reflected in various factual situations. To determine whether the Internet can constitute a public space in the sense of criminal law, several factors must be indicated, including, first of all, the application of an appropriate interpretation of the norms of criminal law.
Keywords: Internet; public place; public act